Commentary on "Promising careers? A critical analysis of a randomised control trial in community health worker recruitment in Zambia, " by James Wintrup. (January 2022) - Ashraf, Nava; Bandiera, Oriana; Davenport, Edward; Lee, Scott S.
Abstract: "Promising careers? A critical analysis of a randomised control trial in community health worker recruitment in Zambia" (Wintrup, 2021) raises important questions about the uses of randomized controlled trials (RCTs) and uses our RCT embedded in Zambia's National Community Health Assistant (CHA) Program (Ashraf et al., 2020a) as a case study to illustrate the pitfalls of the RCT methodology and especially its potential to do harm. This commentary clarifies the misunderstandings at the heart of Wintrup (2021)'s critique.